Stability study of high rise IBS building using STAAD PRO - Engku Muhammad Afnan Engku Azman (School of Environmental Engineering, University Malaysia Perlis, 2013)
This study presents the behavior and stability of high rise building of Industrialised Building System (IBS). STAAD PRO software has been used to analyze the output of the results.